“Home is where theatre is”: Performing Dominican Transnationalism - Camilla, Stevens (Latin American Theatre Review, 2010)
This essay argues that a transnational approach to Dominican performance reveals a wealth of theatrical activity that addresses Dominican-U.S. migration. Like the characters in their plays who perform the social scenarios of migration, the creative endeavors of playwrights and performers such as Elizabeth Ovalle, Zaida Corniel, Chiqui Vicioso, and Josefina Báez are psychically and materially invested in more than one geopolitical space. Framed by critical approaches from Latino theater studies and migration studies, the analysis of the theme of return migration in four pieces by these authors shows that for transnational migrants, “home” can be conceived of as pluri-local and mobile. Their plays thus help to re-conceptualize dominicanidad from a diasporic perspective and to counter stereotyped portrayals of Dominican migration. (CS, Article in English)